2008
DOI: 10.1116/1.2956627
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanoscale CNx/TiAlN multilayered coatings by ion-beam-assisted deposition

Abstract: CN x / TiAlN multilayered coatings with different nanoscale modulation periods and ratio of CN x within each period were prepared by ion-beam-assisted deposition at room temperature. Auger electron spectroscopy ͑AES͒, x-ray diffraction ͑XRD͒, and nanoindenter and a profiler were used to characterize the microstructure and mechanical properties of the coatings. The low-angle XRD pattern and AES indicated a well-defined multilayered structure of the coating. Although monolithic CN x and TiAlN coatings formed amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The Ti/TiN multi-layers consist of repeating layers of two different materials with nano-scale dimensions. The thickness of each successive pair of layers is commonly known as the modulation period, which critically affects the multi-layer properties (Cao et al, 2008). In the present paper, the Ti/TiN multi-layer films were fabricated using PVD with different variations, and the influence on the performance of Ti/TiN multi-layer films due to each single layer period of TiN was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The Ti/TiN multi-layers consist of repeating layers of two different materials with nano-scale dimensions. The thickness of each successive pair of layers is commonly known as the modulation period, which critically affects the multi-layer properties (Cao et al, 2008). In the present paper, the Ti/TiN multi-layer films were fabricated using PVD with different variations, and the influence on the performance of Ti/TiN multi-layer films due to each single layer period of TiN was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have shown that nonequilibrium structure can be presented as a so‐called epitaxial stabilization, affecting nanomultilayers with very thin thickness. For instance, SiC, CN x , and SiN x are forced to crystallize when they are less than certain critical thickness due to the template effect of transition‐metal nitrides . Coatings built through this unusual phenomenon present interest for ultrahard materials.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, SiC, CN x , and SiN x are forced to crystallize when they are less than certain critical thickness due to the template effect of transition-metal nitrides. [5][6][7][8][9] Coatings built through this unusual phenomenon present interest for ultrahard materials. Nevertheless, investigation of this coating configuration concerning the tribological properties is still limited, which should be more valuable for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that multilayer coatings can exhibit high hardness and fracture resistance with low compressive stress through control of the parameters of the layered structure [5,17]. The tribological behavior of carbon-based thin films is also strongly influenced by their chemical composition, polycrystalline structure, and surface morphology [18].…”
Section: Introductionmentioning
confidence: 99%